Influence of the Flo-Dynamics Movement System© intervention on measures of performance in older persons - Carlson LA (Dove Medical Press, 2013)
Lara A Carlson,1 Alexander J Koch,2 Michael Lawrence11University of New England, Biddeford, ME, 2Lenoir-Rhyne University, Hickory, NC, USABackground: Fall-related injuries associated with aging are a serious clinical and economic problem. The Flo-Dynamics Movement System© (FDMS), which consists of eight movements with a water-filled device, may be a useful low-impact exercise suited for older persons. This study investigated the effects of the FDMS regimen with the Wun-Jo™ trainer on measures of strength, flexibility, and balance in older individuals.Methods: In a quasi-experimental study, 15 healthy subjects aged 61–79 years participated in an FDMS exercise program with the Wun-Jo trainer, consisting of three weekly 30-minute sessions. The following measures were assessed pretraining and after 8 weeks of training: knee flexor and extensor isokinetic strength; grip strength; the Short Physical Performance Battery; functional reach; and low back and hamstring flexibility. Data were analyzed using repeated measures analysis of variance, with statistical significance set at the P ≤ 0.05 confidence level.Results: Sit and reach test scores significantly increased (+21%) from baseline to week 8 (P < 0.001). Forward-left functional reach testing significantly increased (P = 0.012), while forward-right functional reach testing did not change (P = 0.474). Both left-lateral (P = 0.012) and right-lateral (P = 0.036) functional reach scores improved. Grip strength increased in both the left (+11.9%) and right (+14.5%) hands (P < 0.001 for each). Isokinetic knee extension at 60° per second increased for the left (+15.6%) and right (+17.6%) significantly (P = 0.001 for each). Isokinetic knee flexion at 60° per second significantly increased for both the left (+43.2%, P = 0.010) and right (+41.7%, P < 0.001). Time to complete the ten-repetition chair stand decreased significantly (-31%, P = 0.004). The 8-feet walk time also significantly decreased (-21.6%, P < 0.001).Conclusion: Participating in the FDMS with the Wun-Jo device may improve balance, low back and hamstring flexibility, walking speed, and knee extensor/flexor and grip strength in older individuals. FDMS training provides an alternative to traditional exercise and offers an effective strategy to increase functional ability in the elderly.Keywords: exercise, aging, balance